Med klasično in digitalno arhivsko teorijo in prakso ter vplivi novih informacijskih tehnologij na delo v arhivih in arhivskih službah pri ustvarjalcih - Klasinc, Peter Pavel (Atlanti, 2023)
Purpose: It is definitely necessary to research and show the connections between classical and digital archival theory and practice, because digitization is discussed and written about a lot today, even though it is already an established activity for archives, archival theory and practice. In archives, archival material has been digitized for many years, primarily for security and further use. The purpose of this paper is to investigate the impact of digitization on the preservation of original archival material. Methodology: Digitization of archival material has been going on for many years. Just like the storage of archival material, digitized material also requires special procedures of usage, storage, migration and the like. By using the experiential method, the paper presents experiences, and above all, the justifications and purpose of digitalization and the use of digitized data. Results: If we want to follow the results of this research, we must first of all analyse the professional and scientific contributions published in the magazine for modern archival theory and practice Atlanti 33 (1, 2) year 2023. In these two issues, one can find many ideas for future diploma thesis at all three levels of archival studies and sciences at Alma Mater Europaea. Conclusion: With the acquired knowledge, it is necessary to upgrade those skills that are closely related to the areas of dealing with archival and documentary material, regardless of whether the material is in physical or digital form. In doing so, we use new information technologies that have a positive impact on the work in the Slovenian public archival network, as well as in the archival services of creators.
Keywords: archival theory and practice; arhivska teorija in praksa; digital archival material; digitalizacija; digitalizat; digitalization; digitalizzazione; digitalno arhivsko gradivo; fizično arhivsko gradivo; informacijske tehnologije; information technologies; materiale archivistico analogico; materiale archivistico digitale; oggetto digitalizzato; physical archival material; teoria e pratica archivistica; TIC